2021
DOI: 10.21203/rs.3.rs-246858/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Administered Subcutaneous Medroxyprogesterone Acetate for Improving Contraceptive Outcomes: A Systematic Review and Meta-Analysis

Abstract: Background: Subcutaneous depot medroxyprogesterone acetate is an easy-to-use injectable contraceptive. A trained person can administer it, including women through self-injection. Objectives: to assess the effectiveness and safety of self-injection versus provider-administered subcutaneous depot medroxyprogesterone acetate for improving continuation of contraceptive use.Search strategy: We searched for randomized controlled trials on November 1, 2020 in Cochrane Central Register of Controlled Trials, MEDLINE, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…DMPA-SC, available in an allin-one prefilled, auto-disabled Uniject ™ injection system known as Sayana ® Press, has been found to be easy to use and suitable for administration by lower-cadre health workers and women themselves [9][10][11]. Recent research has shown that women who self-injected DMPA-SC had significantly higher rates of continuation than those receiving provider-injected DMPA-SC, demonstrating its role as a self-care innovation [12,13]. Self-injection requires fewer clinic visits and, therefore, users may save time and money and may inject themselves in a private location at their convenience.…”
Section: Introductionmentioning
confidence: 99%
“…DMPA-SC, available in an allin-one prefilled, auto-disabled Uniject ™ injection system known as Sayana ® Press, has been found to be easy to use and suitable for administration by lower-cadre health workers and women themselves [9][10][11]. Recent research has shown that women who self-injected DMPA-SC had significantly higher rates of continuation than those receiving provider-injected DMPA-SC, demonstrating its role as a self-care innovation [12,13]. Self-injection requires fewer clinic visits and, therefore, users may save time and money and may inject themselves in a private location at their convenience.…”
Section: Introductionmentioning
confidence: 99%